Challenges in the management of anticoagulated patients with focal spasticity. (15th April 2020) - Boulias, Chris; Ismail, Farooq; Phadke, Chetan P.
Abstract: Introduction: In patients taking warfarin, the level of anticoagulation status using the International Normalized Ratio (INR) is one consideration before botulinum toxin type-A (BoNTA) injections; however, there is wide diversity in physician approaches and preferences in using INR status and the INR cut-off values to determine suitability of anticoagulated patients for BoNTA injections. There is no standard approach for treating spasticity with BoNTA injections in patients who are on warfarin or direct anticoagulants (DOACs). Objective: Our objective was to review the challenges in the use of BoNTA in patients who are receiving anticoagulants and to present highlights of the Canadian Delphi Study on the management of anticoagulated patients with limb spasticity. Methods: We present a hypothetical case of a patient with focal spasticity who is also receiving anticoagulants. Results: The results when injecting BoNTA in anticoagulated patients were as follows: 1) BoNTA injections should not be withheld purely because a patient is anticoagulated and other factors need to be considered. 2) A 25G (or higher) needle should be used when injecting into the deepleg compartment muscles. 3) The INR level ≤3.5 should be used when injecting the deep posterior leg compartment muscles. 4) The concern regarding bleeding when using DOACs remain the same as with warfarin when INR is in the therapeutic range. 6) The dose and scheduling of DOACs need not be altered prior to BoNTA injections. Conclusions: The Canadian consensus statements assist clinicians by providing a framework for consideration to navigate the challenges when injecting BoNTA in anticoagulated patients with spasticity. Highlights: In anticoagulated patients with spasticity, BoNTA injections should be considered When injecting in the deep posterior leg compartment muscles one must exercise caution. If the patient is on warfarin one must ensure that INR is ≤3.5; dose should not be changed for BoNTA treatment purposes. If patient is on direct anticoagulants (DOACs), dose should not be changed for BoNTA treatment purposes A 25G (or higher) needle size along with needle aspiration prior to injecting is recommended.